Dark Noise Suppression of NIR Response Enhanced Si-CMOS Sensor - Ke Wang; Chengxiang Peng; Zuoxun Hou (Photonics, 2022)
We studied the effect of laser fluence on the dark noise performance of a laser-microstructured Si-based CMOS image sensor. The absorption characteristics and crystal properties of the microstructured sensor fabricated under different process conditions were investigated. Furthermore, a short-time etching method capable of improving the electrical performance of the laser-microstructured sensor was proposed. By removing amorphous silicon (a-Si) containing a large number of defects in the photosensitive surface of the microstructured Si-based CMOS image sensor, the etching method can effectively suppress the dark noise of the laser-microstructured Si-photodetector while maintaining the near-infrared response enhancement effect of the Si-photodetector irradiated by fs-laser. The results of the near-infrared imaging test show that on the basis of imaging brightness enhancement, the contrast ratio of the image formed by the CMOS image sensor in the microstructured region etched by RIE under short exposure time is significantly improved.